Sustainable varicose vein therapy using functionalized hydrogels derived solely from livestock waste - Corridon, Peter R.; Ali, Zehara M.; Shibru, Meklit G.; Paunovic, Jovana; Pantic, Igor V.; Preston, Shaun H. (Frontiers in Sustainable Food Systems, 2024)
Developing sustainable and effective treatments for chronic venous insufficiency (CVI) is crucial. In this study, we propose an innovative restorative approach utilizing hydrogels derived from the decellularized extracellular matrix (dECM) from cadaveric vascular tissues, adipose-derived stem cells (ADSCs), and gold nanoparticles (AuNPs). This therapeutic method leverages waste valorization by repurposing discarded cadaveric tissues from slaughterhouse livestock. The dECM hydrogels, enriched with ADSCs and AuNPs, offer a biocompatible scaffold that supports cellular differentiation and vascular integrity. Our approach addresses the limitations of current allo-, auto-, and xenograft methods by enhancing integration and functionality while potentially reducing costs through sustainable practices. This study explores functionalized hydrogel formulation solely generated from agri-food waste, gelation mechanisms, and preliminary cost-effectiveness, presenting a promising new avenue for treating early-stage varicose veins that can ultimately be translated to human models using discarded tissues.